Mean–variance portfolio selection under partial information with drift uncertainty. Issue 9 (2nd September 2021) - Xiong, Jie; Xu, Zuo Quan; Zheng, Jiayu
ABSTRACT: In this paper, we study the mean–variance portfolio selection problem under partial information with drift uncertainty. First we show that the market model is complete even in this case while the information is not complete and the drift is uncertain. Then, the optimal strategy based on partial information is derived, which reduces to solving a related backward stochastic differential equation (BSDE). Finally, we propose an efficient numerical scheme to approximate the optimal portfolio that is the solution of the BSDE mentioned above. Malliavin calculus and the particle representation play important roles in this scheme.